KUALITAS DAN PERSEPSI PENGUNJUNG TAMAN KOTA JALAN DIPONEGORO DAN TAMAN OLAHRAGA DAN REKREASI JALAN YOS SUDARSO PEKANBARU BERDASARKAN GREEN FLAG AWARD - Alfi Puadi; Yusni Ikhwan Siregar; Zulfan Saam (Jurnal Ilmu Lingkungan, 2017)
This research was undertaken between Mei and July 2017 at two locations for public spaces in the Pekanbaru city, namely, the Pekanbaru City Garden (Taman Kota Pekanbaru) in Jalan Diponegoro and Sports Park and Recreation Park Rumbai (TORR) in Jalan Yos Sudarso. The objective of the research is to collect information regarding the condition of city parks and perception available within as well as visitors’ activities on both public spaces based on the Green Flag Award’s standards. This research applied a quantitative method utilizing a respondent perception approach with rating system. Data generated from the rating system were thus interpreted into a qualitative reading. From the field observation at both public parks, researches learnt that visitors made use of them for weekend recreations for family and friends as well as romantic couples. Activities carried out include leisure pastime, parents-children bonding, sport exercises and informal market peddling. The rating score based on Green Flag Award standard as evaluated for Taman Kota Jalan Diponegoro got a value of 1.77 observers and 1.76 observers according to visitor perceptions. TORR Jalan Yos Sudarso 1.76 both from observation and visitor perception. Both parks are categorized as less satisfactory.